Prawo handlowe na Uniwersytecie Wrocławskim - Frąckowiak, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article provides an overview of research and teaching of regulations of private economic relations at the Faculty of Law, Administration and Economics of the University of Wrocław in the last seventy years, against the background of changes in the approach to commercial law in Poland.
Keywords: commercial law; Faculty of Law, Administration and Economics; University of Wrocław; history